ANALISIS PENGETAHUAN MASYARAKAT DALAM MENGGUNAKAN PRODUK BANK SYARIAH (STUDI DESA BONDER KECAMATAN PRAYA BARAT) - Baiq Erma Widiarty; Imronjana Syapriatama; Nurul Susianti (Universitas Islam Negeri Mataram, 2023)
The main thing in this thesis is that the majority of the people of Bonder Village, West Praya Subdistrict, are Muslims, but the people of Bonder Village, West Praya Subdistrict, make more transactions using conventional banks. In this study, the researcher aims to explain and describe the extent of public understanding of Islamic banks and the products available at Islamic banks in Bonder Village, West Praya District. This type of research is descriptive, namely interviews with the community of Bonder Village, West Praya Subdistrict using qualitative methods that describe the community's knowledge of Islamic bank products. Techniques in data collection, the author uses observation, interviews, documentation with the people of Bonder Village, West Praya Subdistrict and data validity assurance techniques the author uses research, namely tringulation theory, after which the author draws conclusions to conclude all the information that has been obtained. The results of the research can be concluded that first, the people of Bonder Village, West Praya Subdistrict generally do not understand the difference between Islamic banks and conventional banks and second, the people of Bonder Village generally do not understand what the products are in Islamic banks.